Diagnostics of mineral nutrition of carrot and red beet at organic and mineral fertilization systems - S. V. Belova (Овощи России, 2024)
Relevance. In the transition to highly productive and environmentally friendly, in particular, organic agriculture and production of safe and high-quality products, which is a priority direction of strategies of scientific and technological development of the Russian Federation, one of the necessary links is the creation and control of optimal conditions of plant nutrition, i.e. provision of plants with nutrients in the right combination throughout the vegetation. Achievement of such conditions is possible through soil and plant nutrition diagnostics, which in turn allows to establish the ability of crops to assimilate nutrients from the soil and adjust the doses of mineral fertilisers as top dressings.Material and Methods. On alluvial meadow soil in the conditions of the non-Black Earth region of Russia, the effectiveness of root feeding with macronutrients (NPK) was studied according to the results of plant and soil diagnostics of table root crops nutrition when grown on organic and mineral fertiliser systems. Plant and soil diagnostics of mineral nutrition was carried out according to the methods of Zerling V.V. (1990) and Magnitsky K.P. (1972). Two crops were tested during the experiment: red beet variety Mulatka and garden carrot variety Losinoostrovskaya 13.Results and Discussion. Root fertilizers on the basis of nutrition diagnostics on the basis of soil and leaf petiole analysis made significant changes in the dynamics of basic nutrients in the soil, there was an increase in nitrate nitrogen and mobile potassium in comparison with the control variant, with natural soil supply of mobile phosphorus (more than 250 mg/kg), which had a positive effect on the root nutrition of plants. At the main application of mineral and organic (biocompost BIUD) fertilizers, root fertilizers according to nutrition diagnostics the carrot yield 51,2-63,9 t/ha with standard 87,4- 94,6%, red beet 41,7-54,2 t/ha with standard 80,7-92,3% were obtained. Root feeding of carrots by soil diagnostics N52K14 on the background of biocompost gave 24.9% increase to the control, by plant diagnostics N17 gave 16.6%; red beet by soil diagnostics N65K45 – 30% increase, by plant diagnostics N54K30 – 23.7%